HUBUNGAN ANTARA RASA PERCAYA DIRI DENGAN KETERAMPILAN DRIBBLING BOLABASKET - Kurnia, Dedi (Jurnal Olahraga, 2019)
The purpose of this study was to determine the relationship between confidence and basketball dribbling skills. The research method used is the correlation method. The correlation studied is bivariate correlation because there are two variables. The object of this study was Scorpio Basketball Club and for the sample were athletes aged 18 years with a sample of 32 people. The results of this study prove that there is a positive and significant correlation between X and Y with a correlation coefficient of 0.73 and a determination index of 53.0%. From the results of data conclusions, there is a positive and significant relationship between confidence and basketball dribbling skills. The results of this study imply that one of the efforts to improve dribbling skills in basketball games is to be confident. But it remains to be remembered that there are still other factors that influence basketball dribbling skills, so further research is needed in the future.